Aplicação de coagulante, de origem vegetal, como alternativa no tratamento de efluentes em uma indústria de saneantes - Bettiol, Bruna (My University, 2022)
The use of coagulant based on aluminum sulfate, together with the flocculant, is an input often used in wastewater treatment, however, as a byproduct, it originates the chemical sludge, containing aluminum salts, which carry with them, a polluting character to the environment. Therefore, the purpose of this study is to evaluate the performance of the tannin-based coagulant, which are biodegradable phenolic molecules extracted from the bark of the Black wattle plant, and apply it to an effluent from a sanitizing industry, through tests in Jar Test. The two initial treatments were performed in the same proportion, both for aluminum sulfate and for the vegetable coagulant, at a dosage of 10 g/L, and finally, in the last treatment, it was decided to reduce the concentration of the vegetable coagulant to 2.5 g/L. In view of the results, the vegetal coagulant at 2.5 g/L reduced physical-chemical parameters with percentages of 60.42 % of turbidity, 70.96 % of phosphorus and 97.95 % of anionic surfactants. Besides having completely eliminated animal and vegetable oils and grease and total suspended solids and, additionally, generating an aluminum-free sludge. The choice of this coagulant does not require pH adjustment in the effluent, it acts both in the coagulation and flocculation process, and it is not necessary to use additional products such as flocculants and alkalinizers, besides presenting better performance in smaller dosages, when compared to aluminum sulfate. Therefore, there is viability in opting for the vegetal coagulant, due to its physical-chemical results, its biodegradable composition and for not requiring high investments or changes in existing projects. [resumo fornecido pelo autor]
O uso de coagulante a base de sulfato de alumínio, em conjunto com o floculante, é um insumo frequentemente utilizado no tratamento de efluentes, entretanto, como subproduto, origina-se o lodo químico, contendo sais de alumínio, que carregam consigo, um caráter poluente ao meio ambiente. Portanto, a proposta deste trabalho é, avaliar o desempenho do coagulante a base de tanino, que são moléculas fenólicas biodegradáveis, extraídas a partir da casca da planta Acácia-Negra, e aplicá-lo em um efluente proveniente de uma indústria de saneantes, por meio de ensaios em Jar Test. Os dois tratamentos iniciais foram realizados na mesma proporção, tanto para o sulfato de alumínio, como para o coagulante vegetal, na dosagem de 10 g/L, e, por fim, no último tratamento, optou-se em reduzir a concentração do coagulante vegetal para 2,5 g/L. Diante dos resultados, o coagulante vegetal a 2,5 g/L reduziu parâmetros físico-químicos com percentuais de 60,42 % de turbidez, 70,96 % de fósforo e 97,95 % dos surfactantes aniônicos. Além de ter eliminado completamente os óleos e graxas animais e vegetais e sólidos suspensos totais e, adicionalmente, gerando um lodo isento de alumínio. A escolha deste coagulante não demanda ajuste de pH no efluente, atua tanto no processo de coagulação, quanto de floculação, não sendo necessário fazer o uso de produtos adicionais como floculantes e alcalinizantes, além de apresentar melhor desempenho em dosagens menores, que comparados com o sulfato de alumínio. Portanto, há viabilidade em se optar pelo coagulante vegetal, devido aos seus resultados físico-químicos, pela sua composição biodegradável e por não exigir investimentos altos ou alterações de projetos já existentes. [resumo fornecido pelo autor]
Keywords: Engenharia química; Saneantes; Coagulantes